A rare presentation of adrenal histoplasmosis in an immunocompetent patient as an adrenal crisis - Sarkar, Abhinandita; Misra, Sourav; Roy, Shuvajit; Roy, Raja; Paul, Dipankar (Indian Journal of Case Reports, 2025)
A 44-year-old diabetic male presented with hypovolemic shock along with cough-cold, weakness, and low-grade fever for the past 4 months. On laboratory investigation, there were hyponatremia, hyperkalemia, and hypercalcemia. Persistently low parathyroid levels along with a positive adrenocorticotropic hormone stimulation test confirmed primary Addison’s disease. On ultrasonography, there was a bilateral adrenal mass over which computed tomography-guided fine needle aspiration cytology was done. Periodic acid Schiff stain of the sample showed intracellular yeast cells resembling histoplasmosis and on culture at 25°C it showed microconidia with successful conversion of mycelium to yeast. The patient was treated with Liposomal Amphotericin B over 2 weeks and steroids, with which the patient gradually improved.